Reflections on "Testing for Unit Roots in Heterogeneous Panels" - Kyung So Im; M. Hashem Pesaran; Yongcheol Shin (Center for Economic Studies and ifo Institute (CESifo), 2023)
This article is our personal perspective on the IPS test and the subsequent developments of unit root and cointegration tests in dynamic panels with and without cross-section dependence. In this note, we discuss the main idea behind the test and the publication process that led to Im, Pesaran and Shin (2003).
Keywords: C01; C23; 330; Dickey and Fuller statistic; stationarity; panel unit root tests; prevalence of unit roots